2004
DOI: 10.1152/japplphysiol.00259.2004
|View full text |Cite
|
Sign up to set email alerts
|

Active hexose correlated compound enhances the immune function of mice in the hindlimb-unloading model of spaceflight conditions

Abstract: Active hexose correlated compound enhances the immune function of mice in the hindlimb-unloading model of spaceflight conditions. J Appl Physiol 97: 1437-1444. First published June 11, 2004 10.1152 10. /japplphysiol.00259.2004 unloading is a ground-based model that simulates some of the aspects of spaceflight conditions, including lack of load bearing on hindlimbs and a fluid shift to the head. It has been shown that treatment with active hexose correlated compound (AHCC) restores resistance to infection in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 35 publications
3
33
0
Order By: Relevance
“…AHCC has been shown to have an enhancing effect on immune function of humans [2,11] and rodents [9,[12][13][14] including an increase of natural killer (NK) cell activity [15], interleukin-12 production [16,17] and resistance to bacterial infection [7,18]. Of interest, it has been found that the effects of AHCC are more evident in hosts with the impaired immune function [18].…”
Section: Introductionmentioning
confidence: 99%
“…AHCC has been shown to have an enhancing effect on immune function of humans [2,11] and rodents [9,[12][13][14] including an increase of natural killer (NK) cell activity [15], interleukin-12 production [16,17] and resistance to bacterial infection [7,18]. Of interest, it has been found that the effects of AHCC are more evident in hosts with the impaired immune function [18].…”
Section: Introductionmentioning
confidence: 99%
“…AHCC has been well tolerated both as a human nutritional supplement and as a therapeutic agent (1,5). Furthermore, several studies have proven that the oral administration of AHCC has a wide variety of therapeutic effects, including anticancer effects both in animal models and in clinical trials (2,3,(6)(7)(8), prevention of the onset of diabetes induced by streptozotocin in animal models (9), prevention of liver injury produced by CCl 4 in mice (10), and improvement of the immune response (7,11,12). The anticancer activity of AHCC has been ascribed to its immunomodulatory and antioxidant properties (4,7,13).…”
Section: Introductionmentioning
confidence: 99%
“…The HDT rat is used as a surrogate for microgravity exposure because this model induces the cephalic fluid shift that occurs in microgravity (10,24,47,59) and HDT rats manifest many of the adaptations that are characteristic of human exposure to microgravity, including hypovolemia (37,51), immune dysfunction (1,8,9,50,52,57), resting and exercise tachycardia (32), a diminished capacity to elevate vascular resistance (32,44), orthostatic hypotension (31), and a reduced aerobic capacity (13,44). Comparative analysis of metabolic and structural shifts in rats after 14 days of microgravity aboard biosatellite Cosmos-2044 and their tail-suspended synchronous controls demonstrated a high correlation of changes in bones and muscles for both experimental groups of animals and provided valuable evidence that HDT can be used as a model of the microgravity effects in ground-based studies (26).…”
mentioning
confidence: 99%